Coinfecção por Papilomavírus Humano e outras infecções sexualmente transmissíveis em amostras cervicais de usuárias da rede SUS de São Luís, Maranhão - CUNHA, Ana Paula Almeida (2019)
Introduction: Human papillomavirus (HPV) is considered the etiological agent of cervical cancer, present in more than 70% of cases. Studies show that persistent HPV infection is facilitated by the presence of other sexually transmitted infections. This association contributes to local chronic inflammation and to the progress of cancer precursor lesions. Thus, the objective of this study was to study the association between HPV infection and the presence of co-infections (Chlamydia trachomatis, Trichomonas vaginalis, and Neisseria gonorrhoeae) in women attending the Primary Health Care (Single Health System) in the state of Maranhão. Material and methods: This is a descriptive and cross-sectional study of 353 women who were participating in women's health programs at Basic Health Units in the period of March/2018 to March/2019. All women agreed to participate in the study by signing an informed consent form and answered a sociodemographic questionnaire. Participants underwent oncotic cytology examination to detect cellular changes in the cervix. After the exam, a cervical swab was collected to perform molecular biology tests for HPV, Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis. HPV DNA was identified using the nested PCR technique using the PGMY09 / 11 and GP5 + / GP6 + primers. Primers KL1 / KL2 (Chlamydia trachomatis), TVA5 / TVA6 (Trichomonas vaginalis) and HO1 / HO3 (Neisseria gonorrhoeae) were used for the identification of other sexually transmitted agents. HPV positive samples were subjected to automated sequencing for viral type identification. Results: Profile of brown women (61.61%), between 35-44 years old (22.2%), with income below 1 minimum wage (84.83%), education through high school (51.66%) and married/stable union (51.66%). There was a high prevalence of HPV (59.7%), of which 147 (69.6%) had HPV infection and other STIs, and 64 (30.3%) had an only HPV infection. In women with T. vaginalis infection, 73.5% had HPV, indicating a statistically significant association between these two pathogens (p<0.05). HPV 16 was more prevalent in both groups; however, high-risk viral types were predominant in women with co-infections, and low-risk viral types were predominant in women with HPV infection only. Women who did not present cervical lesions in the cytological exam were predominant. However, those with lesions also had HPV and other STI coinfection. Conclusion: These findings suggest that the presence of the STI T. vaginalis may favor HPV infection. This HPV/STI association can contribute to the development of cervical intraepithelial lesions precursor of cervical cancer. The results obtained in this study reinforce the importance of the implementation of risk behavior prevention strategies in the population of Maranhão.